Mila ([Metro Manila] Star Cinema, 2001)
Mila is the inspiring story of Mila Cabangon, a teacher who shared her life with those she encountered - empowering them to find their purpose and their potential, and through her example, find ways to realize their mission in life.
Based on the story of Anita Pamintuan.
VHS.
Ricky Lee, screenplay ; producer, Elma S. Medua ; directed by Joel Lamangan.
Maricel Soriano, Cherry Pie Picache, Princess Punzalan, Angelica Panganiban, Serena Dalrymple, Kaye Abad, Piolo Pascual, Jiro Manio.
Keywords: Teachers -- Philippines; Feature films; Drama